Sodium replacement and fluid shifts during prolonged exercise in humans - Sanders, B.; Noakes, T. D.; Dennis, S. C. (European Journal of Applied Physiology, 2001)
In the study presented here, we examined the affects of a close to complete replacement of sweat water and Na+ losses on fluid shifts during exercise. Six cyclists performed three 4-h rides at 55% of their peak oxygen uptake in a 20°C environment while consuming 3.85 l of an 8% carbohydrate solution containing 5, 50 or 100 mEq·l-1 of Na+. Increases in Na+ intake reduced renal free water clearance from around 40 ml·h-1 to -8 and -121 ml·h-1 and led to a decrease in urine volume from 1.0 to 0.5 l (P<0.05). In contrast, the 3.5-3.9 l fluid and 150-190 mEq Na+ losses in sweat were similar in each trial, as were the 80 mEq K+ losses in sweat and urine and the 282-288 mosmol·kg-1 plasma osmolalities. During the low-Na+ trial, plasma osmolality was maintained by a 1.3 l contraction of extracellular fluid (ECF) with the loss of 200 mEq Na+. However, in the other trials, 1.3 l of water was lost from the intracellular fluid. During the medium-Na+ trial, a loss of only 40 mEq Na+ maintained ECF volume, and during the high-Na+ trial, a gain of 160 mEq Na+ expanded the ECF by 0.8 l. However, corresponding changes in plasma volumes from -0.20 to 0.15 l had no effect on cardiovascular drift or thermoregulation. These data suggest that during prolonged exercise of moderate intensity under mild environmental conditions when sweat rates are 0.9 l·h-1, complete Na+ replacement maintains plasma volume and reduces dehydration, but when fluid intake matches sweat rate, has little effect on plasma osmolality.